Jaegwon, Kim. “El fisicalismo no reduccionista y su problema con la causalidad mental.” Trad. Juan Diego Morales. (2015)
Jaegwon, Kim. “El fisicalismo no reduccionista y su problema con la causalidad mental.” Trad. Juan Diego Morales. Ideas y Valores 63.155 (2014): 235-259.